Metaphors in scientific and technical languages: challenges and perspective Metáforas em linguagens técnicas e científicas: desafios e perspectivas - Maria José Bocorny Finatto (DELTA: Documentação de Estudos em Lingüística Teórica e Aplicada, 2010)
This article aims to show, in a summarized way, how different studies on metaphor can positively converge to a cognitive-linguistic perception of this phenomenon. This perception surpasses a merely stylistic vision of the metaphor. The paper also reports the research that was done by Huang (2005) about metaphors in scientific texts of Medicine, which is related to the topic of AIDS. The results and difficulties of Huang's research have given examples in the treatment of the theme of metaphor in Terminology and in studies of scientific texts. It is concluded that metaphor is one of the phenomena that make part of the technical and scientific communication and, because of the complexity in approaching such topic, it must also be investigated in Terminology. O objetivo deste artigo é mostrar, de um modo conciso, como diferentes estudos sobre metáfora podem convergir, positivamente, para uma percepção lingüístico-cognitiva do fenômeno, a qual supera uma visão meramente estilística. Relata-se, com destaque, a pesquisa de Huang (2005) sobre a metáfora no texto científico de Medicina que trata sobre AIDS. Essa pesquisa, em seus resultados e dificuldades, serve como um exemplo para o tratamento da metáfora em Terminologia e em estudos do texto especializado. O artigo conclui que a metáfora é um dos fenômenos que integram a comunicação técnico-científica e que, a despeito da complexidade de sua abordagem, deve ser investigado também em estudos de Terminologia.